2011
DOI: 10.1111/j.1467-629x.2010.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Fifty-year overview of judgment and decision-making research in accounting

Abstract: As part of the celebration of the fiftieth anniversary of AFAANZ, we consider the breadth of judgment and decision-making (JDM) experimental research in accounting over that 50-year period. Our review is divided by decade and between auditing, financial accounting and management accounting. In four major journals, we found 5745 papers between 1970 and 2009, which we consider impressive and strong support for the opportunity to publish in this field. Our aim is to encourage more JDM research from Australians an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
20

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 381 publications
1
74
0
20
Order By: Relevance
“…Suatu hal yang menarik adalah dominasi metode eksperimen atas RKDA (Swieringa dan Weick 1982 Trotman et al (2011). Namun demikian, perkembangan riset eksperimental pengauditan sebagai rerangka penelitian di bidang pengauditan serta sintesis topik kontemporer masih belum disajikan dalam riset terdahulu (Trotman 2011;Trotman et al 2011).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Suatu hal yang menarik adalah dominasi metode eksperimen atas RKDA (Swieringa dan Weick 1982 Trotman et al (2011). Namun demikian, perkembangan riset eksperimental pengauditan sebagai rerangka penelitian di bidang pengauditan serta sintesis topik kontemporer masih belum disajikan dalam riset terdahulu (Trotman 2011;Trotman et al 2011).…”
Section: Pendahuluanunclassified
“…Menurut Trotman et al (2011), terdapat enam tema penting yang mendominasi riset audit pada awal 1980an. Pertama, kelanjutan policy capturing research oleh Ashton (1974).…”
Section: Fase 1980anunclassified
See 1 more Smart Citation
“…If this happens, then the next risk on management budgetary will halt because of the volatility expenditure occurred in the department. Trotman (2011) argued that social concerns might reduce the need for extensive incentive contracting.…”
Section: Impact Of Remuneration On Management Behaviormentioning
confidence: 99%
“…Research about decision making on specific accounting policy is based on Trotman (2011) who suggested that the research on the judgment and decision making in accounting can be inferred from management motivation in which the impact of personality factors on motivation should also be investigated. Hunton et.al (2008) found that audit committee lacks monitoring in revenue recognition under SEC requirement because of tied-up directors, but they do not explain reason or motivation of tied-up-directors such private issues or have another project gives higher incentives or remuneration matter.…”
Section: Impact Of Remuneration On Management Behaviormentioning
confidence: 99%